Masterbatch-enabled acceleration of polyolefin biodegradation under open air terrestrial environmental conditions - Kütahya,C; Pániker,CC; Ly,F; Jerath,A; Little,E; Gali,R; Haimi,MZBD; Malek,AHBA; Muhamad,KB; Supian,SB; Young,TB; Lawrence,S; et al. (npj Materials Degradation, 2026)
Polyolefins, commonly used in packaging and single-use products, are notoriously persistent in the environment, contributing significantly to environmental pollution. In scientific literature to date, polyolefins have not been reported to fully biodegrade. This study examines the biodegradation potential of polyolefin materials, specifically polyethylene (PE) and polypropylene (PP), enhanced through the incorporation of Biotransformation Masterbatch technology. The inclusion of the Biotransformation Masterbatch accelerated and enabled the full biodegradation of PE and PP, as demonstrated by laboratory weathering, and biodegradation studies in soil at mesophilic temperatures. Ecotoxicity tests revealed no adverse effects on test organisms in both soil and water environments, while metagenomics analysis demonstrated that biodegradation of these polyolefins did not significantly change the soil microbiota composition, which showed higher metabolic activity compared to virgin plastic controls. These findings demonstrate that Biotransformation technology provides an effective solution for delivering polyolefin-based materials with reduced environmental impact. It offers a sustainable alternative to conventional plastics, preserving the performance characteristics of traditional polyolefins while addressing the problem with fugitive plastic waste in the environment.